Achaemenid ceramics from the site Beniamin II (Shirak, Armenia): the end of the 6th to the mid 4th centuries BC - Fichet de Clairfontaine, François; Deschamps, Stéphane (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
In Beniamin, not far from Gyumri, Armenia, at the foot of a hill on which an Achaemenid palace was built, several semi-excavated constructions dating back from the 6th-4th centuries BC were found. Hosting metallurgy workshops at the beginning of their existence, they were later the seat of a livestock activity. From artisanal iron workshop to long-house, they offer a double interest: They concern the economy of an Achaemenid palatial domain, and present a typical architecture of the Armenian plateau, very similar to the houses described by Xenophon in the 5th century BC, in the Anabasis, the epic of the Ten Thousand. Finally, six main periods of occupation were highlighted by the analysis of stratigraphic data and archaeological artifacts discovered. Continuing the first article devoted to architecture and its evolution, this contribution aims to present the catalogue of the productions collected in the Achaemenid levels of periods I to V. The evolution of these productions clearly attests the function of the buildings demonstrating essential similarities to that of the contemporary site of Tsaghkahovit. After the rapid disappearance of coarse and often decorated common forms (decorated black pottery – group 1A), the present catalogue of Achaemenid ceramics is mainly characterized by productions with red slip (Type 3), black common wares (Type 1b and C), with special predominance of productions of brown burnished ware (clear or polished – type 4). Painted ceramics are almost absent from the catalogue of productions.